MIDWIFERY CARE FOR WOMEN IN LABOR WITH SECOND-DEGREE PERINEAL TEARS AT THE SARFINA PRATAMA CLINIC - Hasibuan, Vivi Restiani; Juliana Munthe; Naomi Hutasoit; Lenny Rayana Katarina Sitanggang; Sarfina Sembiring, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Normal delivery is the physiological process of delivering the fetus, placenta, and amniotic membranes from the uterus at term gestation, namely 37–42 weeks, which occurs spontaneously through the birth canal without complications (WHO, 2025). However, complications of childbirth are still common, one of which is perineal tears that can cause postpartum pain and reduce the mother's quality of life. The high global maternal mortality rate, which is still at 197 per 100,000 live births in 2023, emphasizes the importance of improving the quality of obstetric services, including in managing complications of childbirth (Statistical Compendium, 2025). Second-degree perineal tears are the most common type that occurs in normal deliveries, especially in primiparas. Their occurrence is influenced by factors such as parity, birth weight of the baby, pushing techniques, and the skills of the birth attendant. Appropriate treatment is needed to prevent further complications, such as infection and impaired wound healing. This report aims to describe the management of midwifery care for mothers giving birth with second-degree perineal tears at the Sarfina Primary Clinic, North Sumatra Province in 2026.method: used is a case study with a midwifery management approach that includes assessment, diagnosis formulation, planning, implementation, and evaluation of care. Results: show that comprehensive and standardized midwifery care starting from identifying risk factors, correct delivery assistance techniques, to suturing and caring for perineal wounds can accelerate healing and prevent complications. Conclusion: Appropriate and continuous midwifery care management is very important in the management of second-degree perineal tears to improve maternal health and safety in the postpartum period..